Topoisomerase 1 Regulates Gene Expression in Neurons through Cleavage Complex-Dependent and -Independent Mechanisms - Mabb, Angela M. (PLoS One, 2016)
Topoisomerase 1 (TOP1) inhibitors, including camptothecin and topotecan, covalently trap TOP1 on DNA, creating cleavage complexes (cc’s) that must be resolved before gene transcription and DNA replication can proceed. We previously found that topotecan reduces the expression of long (>100 kb) genes and unsilences the paternal allele of Ube3a in neurons. Here, we sought to evaluate overlap between TOP1cc-dependent and -independent gene regulation in neurons. To do this, we utilized Top1 conditional knockout mice, Top1 knockdown, the CRISPR-Cas9 system to delete Top1, TOP1 catalytic inhibitors that do not generate TOP1cc’s, and a TOP1 mutation (T718A) that stabilizes TOP1cc’s. We found that topotecan treatment significantly alters the expression of many more genes, including long neuronal genes, immediate early genes, and paternal Ube3a, when compared to Top1 deletion. Our data show that topotecan has a stronger effect on neuronal transcription than Top1 deletion, and identifies TOP1cc-dependent and -independent contributions to gene expression.